2016
DOI: 10.1101/084525
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isoflurane produces antidepressant effects and induces TrkB signaling in rodents

Abstract: A brief burst-suppressing isoflurane anesthesia has been shown to rapidly alleviate symptoms of depression in a subset of patients, but the neurobiological basis of these observations remains obscure. We show that a single isoflurane anesthesia produces antidepressant-like behavioural effects in the learned helplessness paradigm and regulates molecular events implicated in the mechanism of action of rapid-acting antidepressant ketamine: activation of brain-derived neurotrophic factor (BDNF) receptor TrkB, faci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Our study of the effects of propofol anesthesia on PS rates measured in vivo indicated that Fmr1 KO, but not WT, mice responded to propofol anesthesia with altered rates of overall PS (Qin et al ). Moreover, work of others has shown lasting effects of quickly cleared anesthetics such as isoflurane and halothane in WT mice on the activation of proteins such as ERK, mTOR, eIF2α, and p70S6K (Palmer et al ; Qin et al ; Antila et al ; Kang et al ). These proteins are involved in the regulation of PS and are thought to be involved in the group 1 mGluR response.…”
Section: Discussionmentioning
confidence: 99%
“…Our study of the effects of propofol anesthesia on PS rates measured in vivo indicated that Fmr1 KO, but not WT, mice responded to propofol anesthesia with altered rates of overall PS (Qin et al ). Moreover, work of others has shown lasting effects of quickly cleared anesthetics such as isoflurane and halothane in WT mice on the activation of proteins such as ERK, mTOR, eIF2α, and p70S6K (Palmer et al ; Qin et al ; Antila et al ; Kang et al ). These proteins are involved in the regulation of PS and are thought to be involved in the group 1 mGluR response.…”
Section: Discussionmentioning
confidence: 99%
“…As shown above, fluorescent immunolabeling allows the detection of several molecules in a single section without losing spatial information and provides functional insight thanks to that spatial relationship. Examples of this relationship are the detection of certain molecules expressed in the nucleus within a specific calcium binding protein neuronal subpopulation ( Antila et al., 2017 ), the detection of synaptic proteins in overlap with an inhibitory or excitatory neurotransmitter transporter ( Guirado et al., 2012 ; Sánchez-Huertas and Rico, 2011 ) or the study of the perisomatic innervation of certain subpopulations of neurons ( Favuzzi et al., 2017 ; Fazzari et al., 2010 ; Guirado et al., 2014 ; Kobayashi et al., 2010 ). On the other hand, in clinical studies immunofluorescence imaging is delivering more promising results regarding multiplexing: studying expression levels of protein clusters from a single sample ( Alonso et al., 2004 ; Makretsov et al., 2004 ), suggesting our macros could be used in the clinic for a better diagnosis in human samples as well.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that nitrous oxide ("laughing gas"), an NMDAR-blocking anesthetic possessing rapid antidepressant potential (Nagele et al, 2015), increases markers of cortical excitation, including the expression of immediate early genes (IEGs) such as c-Fos (Fos protooncogene), Arc, and Homer1 (homer protein homolog 1) (Kohtala et al, 2019b). Whether other anesthetics with antidepressant potential, such as isoflurane (Langer et al, 1995;Weeks et al, 2013;Antila et al, 2017) or propofol (Mickey et al, 2018), also regulate cortical excitation in a similar manner remains to be investigated. Several reports have, however, highlighted the paradoxical excitation that frequently takes place during general anesthesia, characterized by a pattern of burst-suppression in the cortical EEG (Kroeger and Amzica, 2007;Ferron et al, 2009).…”
Section: Examining Rapid Antidepressant Effects Through Encodingmentioning
confidence: 99%